Pengaruh Kinerja Keuangan Terhadap Return Saham (Studi Empiris Pada Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Sofi’yah Sofi’yah; Budi Wahono; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTReturn of shares is the profit gained from the ownership of the investor's share of theinvestment. In this study will be discussed about how the influence of financial ratios on theperformance of companies that affect stock returns "The Effect of Financial Performance onStock Return (Empirical Study on Food and Beverage Sectors Listed on Indonesia StockExchange Period 2014-2016)" This study aims to determine The influence of financialperformance as measured by Earning per Share (EPS), Return On Equity (ROE), and Debt toEquity Ratio (DER) to stock return either simultaneously or partially.The method of data collection is by downloading the annual financial statements ofeach sample, whose data has been published by the research division of development ofIndonesia Stock Exchange.Keywords: Earning per Share (EPS), Return On Equity (ROE), and Debt to Equity Ratio(DER), stock return.